Review: Emerging sensors and instrumentation systems for bovine health monitoring - C. Ferreira; M. Todorovic; P. Sugrue; S. Teixeira; P. Galvin (Animal)
This literature review examines the latest and emerging technologies used for monitoring bovine health. Global demand for animal products underscores the need to monitor livestock well-being for enhanced efficiency in the dairy industry and product quality. The study identifies the relevant parameters for monitoring and evaluating commercially available products and cutting-edge technologies. The study highlights key performance features of these technologies, such as communication protocol, size, and battery lifetime. The review also examines current and emerging sensor systems, such as smart boluses and wearable systems that can provide valuable information on bovine welfare, early disease detection, and animal tracking on the farm. By exploring the state-of-the-art technologies in this field, this literature review provides insights into the best technology solutions available for monitoring bovine health and elaborates potential future challenges and opportunities for creating an ideal bovine health monitoring system.